Total factor productivity change of the Malaysian Islamic banking sector: an empirical study - Sufian, Fadzlan (Islamic Bank Training and Research Academy, Islamic Bank Bangladesh Limited, 2009)
The paper seeks to examine the antecedents of the Malaysian Islamic banking sector’s productivity changes during the period 2001-2005. The study employs the Malmquist Productivity Index (MPI) method to isolate efforts to catch up to the frontier (efficiency change) from shifts in the frontier (technological change) and the main sources of efficiency changes. The empirical findings suggest that the Malaysian Islamic banking sector have exhibited productivity regress mainly due to the decline in technological change. This study finds that the foreign IBS banks have exhibited lower productivity levels compared to their domestic peers. The results suggest that the domestic Islamic Banking Scheme (IBS) banks have exhibited higher productivity levels compared to their foreign peers attributed to higher technological progress and efficiency levels.